1989
DOI: 10.3109/17453678909150113
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor problems after cervical spine injury

Abstract: Oculomotor function was investigated in 39 patients with a previous soft-tissue injury of the cervical spine. The velocity, the accuracy, and the pattern of the eye movements were disturbed in 20 patients with chronic and disabling symptoms. Oculomotor function in the 19 asymptomatic patients did not differ from a control group. The oculomotor function seems to be impaired, possibly by brain stem lesions, in patients with chronic symptoms of whiplash injury of the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
3
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 9 publications
2
28
3
1
Order By: Relevance
“…Recently, we reported on oculomotor dysfunction in 18 of 20 cases with chronic symptoms after soft-tissue injury of the cervical spine (Hildingsson et al 1989). 13 of the 18 cases with persisting symptoms in the ------ Animal experiments have shown that noncontact injury of the cervical spine might result in pathologic alterations in the central nervous system, especially in the brain stem region (Domer et el.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported on oculomotor dysfunction in 18 of 20 cases with chronic symptoms after soft-tissue injury of the cervical spine (Hildingsson et al 1989). 13 of the 18 cases with persisting symptoms in the ------ Animal experiments have shown that noncontact injury of the cervical spine might result in pathologic alterations in the central nervous system, especially in the brain stem region (Domer et el.…”
Section: Discussionmentioning
confidence: 99%
“…The oculomotor tests were performed by the method described by Hildingsson et al (1989). The control group's mean f 2 SD was considered to be the normal value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, EEG is not regarded as meaningful in the evaluation of patients with whiplash injury. Several studies have shown that impaired voluntary eye movements may occur in the acute phase as well as among patients with persistent complaints after whiplash trauma [77,93,98,100,207]. The causes of these changes could be multiple, but in some patients the results were interpreted as indicating brain stem dysfunction.…”
Section: Central Nervous Systemmentioning
confidence: 98%
“…Mareo o inestabilidad: el mareo o la inestabilidad es un síntoma muy común en los latigazos cervicales. En un estudio de Hildingsson et al [67] se describe un grupo de 20 pacientes con SLC, de al menos un año de evolución, 18 pacientes presentaban algún tipo de sensación de inestabilidad o vértigo.…”
Section: Patología Asociada Al Nivel I De La Escala De Quebecunclassified